Subextension and approximation of m-subharmonic functions with given boundary values - Amal, Hichame; El Gasmi, Ayoub (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We establish a result on subextension of m-subharmonic functions in the class F_m(Ω,f) without changing the Hessian measures. As application, we approximate an m-subharmonic function with given boundary value by an increasing sequence of m-subharmonic functions defined in larger domains.